The Multiple Temporalities of Epidemic Endings - Wigen, Einar (Centaurus, 2022)
Abstract The beginnings of epidemics are often told as if they are simple to locate in time. They take the form of a crisis, and as such, function as great synchronisers of different temporalities, bringing social temporalities “in line” with biological ones. In the case of the COVID-19 pandemic, for example, political processes that are usually slow were accelerated in order to “catch up with” the fast pace of the virus's reproduction, as policymakers saw a need to contain the virus. The end of an epidemic, on the other hand, is more difficult to pinpoint. This can be attributed to the fact that the myriad actors involved in and affected by an epidemic operate on diverging time scales. Although seemingly synchronised from its outset, these lifetimes become un-synchronised as the epidemic unfolds. Some effects of an epidemic outbreak are easily observed, such as infection rates and the number of deceased. Others-psychological or medical after-effects, or the lasting memory in a population-may be harder to spot. Declaring that an epidemic has “ended” usually relies on the ceasing of the former, not the latter. However, as this article argues, the ending(s) of an epidemic should be regarded in the plural, each operating within its own rhythm and scale. This article explores the multiplicity of lifetimes involved in epidemics-human, microbial, institutional-and tries to give an explanation as to how epidemics end (or linger on) using an approach of multiple temporalities.